SYNTHESIS OF NOVEL 3D MICROENVIRONMENT USING ECM-ENHANCED COLLAGEN-PEG-A HYDROGEL - Mischo, Seth H (Wake Forest University, 2022)
The causes of the cellular dysfunction that impedes tissue regeneration are not well understood and are often multi-factorial but are associated with major tissue trauma such as in volumetric muscle loss (VML). Outcomes vary in severity; however, these conditions can lead to loss of limb function, deformity, and disability. There are relatively few reliable models to research such a disorder and fewer treatments available to overcome loss of function. Bioengineering has several promising avenues for treatments through tissue specific biomaterial development such as incorporating key micro-environmental and mechanical properties necessary for normal cellular function. In this thesis we developed a hydrogel augmented with extracellular matrix and seeded with adipose derived stem-like cells (ADCs) to provide the groundwork for a regenerative medicine approach utilizing a cell type found in the periphery of skeletal muscles. We hypothesize that incorporation of decellularized extracellular matrix (ECM) into collagen-poly (ethylene-glycol)-acrylate (CPA) hydrogels will provide a stable and survivable environment for ADCs.CPA, and Collagen-Peg-A-ECM (CEPA) hydrogels were assessed via rheology and exhibited varying levels of structural rigidity and storage modulus was modeled using a multiple linear regression (MLR) model and an additive model. ADCs encapsulated in both CPA and CEPA hydrogels showed differences in cell viability.
Keywords: 3D Microenvironment; Collagen; Hydrogel; Polyethylene Glycol